Insights into inter-story isolation design through the analysis of two case studies. (15th July 2020) - Faiella, Diana; Mele, Elena
Highlights: The IIS is reviewed and classified within the isolation and mass damping approaches. Two real buildings are examined in view of the approaches provided in literature. Simplified models are adopted for assessing the seismic behavior of the buildings. Abstract: Inter-story isolation system (IIS, also appointed as mid-story isolation), is currently spreading and gaining significant popularity, mainly in Japan. However, while more than sixty applications have been realized in nearly twenty years, the conceptual framework for dealing with the design problem of IIS is not well established, since the IIS combines isolation and mass damping control strategies. In this paper two case studies of real inter-story isolated buildings are in depth examined for interpreting the latest design practice in the light of approaches and indications coming from the world of research. The two buildings, very different from each other, cover the wide applicability of IIS. One of them is a paradigmatic example of ideal IIS, with dynamic characteristics commonly adopted in the scientific community, i.e. a very rigid superstructure, and frequencies of the two structural parts well separated from the isolation frequency. The other building is a non-typical case of IIS, with the upper structures less rigid than the lower one, and both structural portions quite flexible. Modal and frequency response analyses are carried out on simplified two- or three- degree-of-freedom models, representing the reduced-order models utilized in the inherent scientific literature for grasping the influence of the main design parameters governing the dynamic problem. Modal and non-linear time history analyses are then carried out on multi degree-of-freedom models, for the seismic assessment of the buildings. The main results are reported and design implications are discussed.